Evaluation of discontinuity and opening geometry effects on roof beam deflection - Moussaei, N.; Sharifzadeh, Mostafa; Shahriar, K.; Khosravi, M. (2016)
Discontinuity geometry and its mechanical properties as well as opening dimensions influence the instability of the shallow underground excavations. Due to wide range of bedding structures, in this research authors tried to analyses such structure using small scale experimental and numerical models. In the tested models beddings dip varies from 0, to 90 degrees. Layer thickness is considered 16 millimeters. The tunnel width and height are considered 10, 12, and 14 times as big as the bedding thickness. Also the joint spacing is one to two times as big as the bedding thickness. Due to both low stress level and high span compared to layer thickness ratio, only buckling failure potentially occurs in roof beams. Test results show that, along with span to layer thickness ratio, bedding dip as well as sinusoidal component of layer weight affect the magnitude of deflection. Image were taken during tests and processes to measure the roof beam deflection. Model test results show that existing theories (for large deflection) predict the roof beam deflection bigger than what occurred in real condition. Finally, based on the captured results, voussoir beam theory reformed by considering the sinusoidal component of layer weight and bedding dip. Due to There is Uncertainty about ground properties, this theory predict upper and lower bound of roof beam deflection based on data obtained from physical and numerical results.